Specters of Frye - Lavagnino, Nicolás Alejo (2014)
The influence of Northrop Frye’s Anatomy of Criticism in White’s work is evident from the very moment that the reader begins to read the Introduction to Metahistory. Frye appears there as providing a kind of vocabulary for the analysis of historical narratives, focusing on the concept of emplotment. But it can be said that in the face of the plurality of critical theories contained in Frye’s Anatomy, White has proceeded, from Metahistory onwards, in a cautious, even restrictive fashion, generating an artificial division between the vocabulary of ideological implication and that of emplotment. This caution, I argue, has restricted much of the potential and utility of Frye’s critical specters for a historical narratology. The exclusive focus on emplotment in White’s work has an important role, which is to reinforce the distinction between the tropological deep base and the surface strategies of which plots and implications are two of the dimensions surveyed. Yet, as a result of the commitment to the idea of a tropologically informed depth, we get a curious amputation of Frye’s theory of muthos in order to make space for this artificial distinction. But narrativism should not generate these false dilemmas. White’s philosophy of history and Frye’s literary theory tend to converge on a view of language that places it in a continuous social praxis within the variable spectrum of human behavior. It is for this reason that in the end I suggest to adopt the framework of “radical interpretation”, present in the philosophy of language of Donald Davidson, as a way to enrich this perspective and deepen what I call broad muthos theory.